Interaction of water deficit, canopy modification and ripening : effect on the phenolic and colour composition of Shiraz grapes & subsequent wine - Van Noordwyk, Marelize (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2012.